ANALISIS FILSAFAT PENDIDIKAN KI HADJAR DEWANTARA (KHD) DAN IMPLEMENTASINYA DALAM PENDEKATAN DEEP LEARNING - ayudewi, permata; ismail, ismail (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This research analyzes the implementation of Ki Hajar Dewantara's educational philosophy in the Deep Learning approach. Ki Hadjar Dewantara's educational philosophy is rooted in ideology and local wisdom, emphasizing the aspects of character development (budi pekerti), intelligence, and physical health, with the goal of forming individuals with noble character, culture, and competence. The research method used is qualitative with a literature review approach. The researcher sought references and then analyzed the implementation of Ki Hadjar Dewantara's educational philosophy. The results of the study show that Ki Hadjar Dewantara's philosophy is deeply aligned with Deep Learning, which is implemented through the concepts of Meaningful learning, Mindful learning, and Joyful learning. This integration focuses on the personalization of learning to realize Ki Hadjar Dewantara's humanism. Ki Hadjar Dewantara's holistic education concept, which includes Intellectual Development (Olah Rasio /Cipta/ Thought), Emotional/ Character Development (Olah Rasa/ Karsa/ Heart), and Physical/ Skill Development (Olah Raga/ Karya/ Body), is effectively supported by Deep Learning. Deep Learning supports Intellectual Development through critical and deep thinking, Emotional/ Character Development through Ing Madya Mangun Karsa to evoke spirit and character, and Physical/Skill Development through Tut Wuri Handayani which encourages independence and skills. Although the Deep Learning approach has advantages in developing deep understanding and critical thinking, its implementation faces challenges such as limited infrastructure, teacher readiness, and adherence to traditional curricula. Solutions include the need for professional development for teachers and the integration of character values and digital ethics, in line with Ki Hadjar Dewantara's principle of Ing Ngarsa Sung Tuladha. By combining Ki Hadjar Dewantara's philosophy and Deep Learning, education in Indonesia has a great opportunity to create a system that is holistic, adaptive, creative, character-driven, and relevant to the demands of the times, without abandoning cultural roots.